Abstract Time and Affective Perception in the Sonic Work of Art. (September 2014) - Ikoniadou, Eleni
The purpose of this article is to explore the concept of rhythm as enabling relations and thus as an appropriate mode of analysis for digital sound art installation. In particular, the article argues for a rhythmanalysis of the sonic event as a 'vibrating sensation' (Deleuze and Guattari) that incorporates the virtual without necessarily actualizing it. Picking up on notions such as rhythm, time, affect, and event, particularly through their discussion in relation to Susanne Langer's work, I argue for the consideration of the sonic event as an instance of a different kind of temporality subsisting underneath clock-time and sense perception. Ultimately, and this is the position of this essay, an investigation into experimental projects that interweave digital, sound, and aesthetic dimensions enables the articulation of a rhythmic time that helps account for the unknown, indeterminate, and unintentional forces immanent to the sonic.